Firm-to-firm financial linkages and dollar risk transmission - Hardy, Bryan; Saffie, Felipe; Simonovska, Ina (Journal of Financial Economics, 2026)
We study how U.S. dollar fluctuations transmit through domestic supply chains in emerging markets. Large firms borrow in foreign currency and extend trade credit to domestic partners, exposing the supply chain to exchange rate risk. We develop a model where financially constrained suppliers pass through shocks to buyers, while unconstrained firms absorb them. Using quarterly firm-level data from 19 emerging markets, we provide empirical evidence consistent with the model’s predictions. We find that even highly exposed firms reduce trade credit only modestly following a depreciation, while accepting large profit losses, suggesting that firm-to-firm credit relationships partially shield downstream firms from financial shocks.